2020
DOI: 10.1111/apt.16026
|View full text |Cite
|
Sign up to set email alerts
|

Predictors and outcomes of histological remission in ulcerative colitis treated to endoscopic healing

Abstract: Summary Background Clinical remission is the recommended treatment target in ulcerative colitis. The predictors and outcomes of achieving histologic remission within a treat‐to‐target paradigm are not well established. Aim To evaluate the predictors and outcomes of achieving histologic remission in patients with ulcerative colitis treated‐to‐target of endoscopic healing (modified Mayo endoscopy score 0 or 1). Methods We conducted a retrospective cohort study in adults with active ulcerative colitis (modified M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 18 publications
4
27
0
Order By: Relevance
“…In our cohort, we suggested that histologic remission only has benefit in patients with MES = 1 disease, with no further benefit noted in patients who attain MES = 0 disease 2 . Our findings do not conflict with Maeda et al, but support that achievement of histologic remission in MES = 1 endoscopic disease provides benefit over and above attaining MES = 1 disease alone.…”
Section: Figuresupporting
confidence: 56%
See 2 more Smart Citations
“…In our cohort, we suggested that histologic remission only has benefit in patients with MES = 1 disease, with no further benefit noted in patients who attain MES = 0 disease 2 . Our findings do not conflict with Maeda et al, but support that achievement of histologic remission in MES = 1 endoscopic disease provides benefit over and above attaining MES = 1 disease alone.…”
Section: Figuresupporting
confidence: 56%
“…The authors' declarations of personal and financial interests are unchanged from those in the original article. 2…”
Section: Ack N Owled G Em Entmentioning
confidence: 99%
See 1 more Smart Citation
“…We read with great interest the article by Jangi et al who reported that histologic remission was associated with favourable outcomes in patients with a Mayo endoscopic subscore (MES) of 1 1 . The article provided useful information for setting the treatment target in ulcerative colitis (UC); however, we would like to ask the authors whether they conducted a direct comparison of the cumulative risks of symptomatic relapse between patients achieving both histologic remission and MES = 1 and those with MES = 0.…”
Section: Figurementioning
confidence: 99%
“…As described above, different studies have positively evaluated the validity and reliability of the endoscopic criteria that are commonly used for UC today. However, in several cases, ER was observed without full achievement of histological remission [14][15][16]. Some reports describe that the histological activity and endoscopic activity are correlated [17,18] but endoscopic findings with a low activity must be assessed for patients who have achieved histological remission.…”
Section: Introductionmentioning
confidence: 99%